Compositional flexibility in Li–N–H materials: implications for ammonia catalysis and hydrogen storage. Issue 28 (7th July 2021) - Makepeace, Joshua W.; Brittain, Jake M.; Sukhwani Manghnani, Alisha; Murray, Claire A.; Wood, Thomas J.; David, William I. F.
Abstract : A wide solid solution based on the lithium imide anti-fluorite structure is demonstrated and related to its energy storage functions. Abstract : Li–N–H materials, particularly lithium amide and lithium imide, have been explored for use in a variety of energy storage applications in recent years. Compositional variation within the parent lithium imide, anti-fluorite crystal structure has been related to both its facile storage of hydrogen and impressive catalytic performance for the decomposition of ammonia. Here, we explore the controlled solid-state synthesis of Li–N–H solid-solution anti-fluorite structures ranging from amide-dominated (Li4/3 (NH2 )2/3 (NH)1/3 or Li1.333 NH1.667 ) through lithium imide to majority incorporation of lithium nitride–hydride (Li3.167 (NH)0.416 N0.584 H0.584 or Li3.167 NH). Formation of these solid solutions is demonstrated to cause significant changes to the thermal stability and ammonia reactivity of the samples, highlighting the potential use of compositional variation to control the properties of the material in gas storage and catalytic applications.